Safety of Tocilizumab in COVID-19 Patients and Benefit of Single-Dose: The Largest Retrospective Observational Study - Ayman M. Al-Qaaneh; Fuad H. Al-Ghamdi; Sayed AbdulAzeez; J. Francis Borgio (MDPI AG, 2022)
Severe acute respiratory coronavirus-2 (SARS-CoV-2) still presents a public threat and puts extra strain on healthcare facilities. Without an effective antiviral drug, all available treatment options are considered supportive. Tocilizumab as a treatment option has to date shown variable results. In this retrospective study, we aimed to assess predictors of mortality of COVID-19 patients (n = 300) on tocilizumab and the clinical effectiveness of this drug. The results showed that ICU admission OR = 64.6 (95% CI: 8.2, 507.4); age of the patient OR = 1.1 (95% CI: 1.0, 1.1); and number of tocilizumab doses administered by the patient OR(two doses) = 4.0 (95% CI: 1.5, 10.9), OR(three doses) = 1.5 (95% CI: 0.5, 5.1), and OR(four doses or more) = 7.2 (95% CI: 2.0, 25.5) presented strong correlation factors that may be linked to COVID-19 mortality. Furthermore, our study showed the beneficial effects of early administration of tocilizumab OR = 1.2 (95% CI: 1.1, 1.4) and longer hospital length of stay OR = 0.974 (95% CI: 0.9, 1.0) in reducing COVID-19 mortalities. High blood D-dimer concentration OR = 1.1 (95% CI: 1.0, 1.2) and reciprocal blood phosphate concentration OR = 0.008 (95% CI: 0.0, 1.2) were correlated to high mortality under SARS-CoV-2 infection. The short-term effect of a single dose of tocilizumab was a significant increase in blood BUN and liver enzymes (ALT, AST, and LDH) above their normal ranges. Furthermore, it significantly reduced CRP blood concentration, but not to normal levels (13.90 to 1.40 mg/dL, p < 0.001). Assessing the effect of different doses of tocilizumab (in terms of the number of doses, total mg, and total mg/kg administered by the patients) indicated that administering more than one dose may lead to increases in ICU length of stay and hospital length of stay of up to 14 and 22 days after the last dose of tocilizumab (6 to 14, p = 0.06, and 10 to 22, p < 0.001), with no improvement in 28- and 90-day mortality, as confirmed by Kaplan-Meier analysis. There were also clear correlations and trends between the number of doses of tocilizumab and increased blood CO2, MCV, RDW, and D-dimer concentrations and between number of doses of tocilizumab and decreased CRP, AST, and hemoglobin concentrations. Microbiology analysis showed a significant increase in the incidence of infection after tocilizumab administration (28 to 119, p < 0.001) with a median time of incidence within 6 days of the first dose of tocilizumab. A significant correlation was also found between the number of tocilizumab doses and the number of incidences of infections after tocilizumab administration r (298) = 0.396, p = 1.028 × 10−12. Based on these results and depending on the pharmacokinetic parameters of the drug, we recommend single-dose administration of tocilizumab as the optimal dosage for COVID-19 patients who do not have active bacterial infection or liver diseases, to be administered as soon as the patient is admitted to the hospital.